Prospects of amaranth using in the brine systems based on uronate polysaccharides - Kondratiuk, Natalia Vyacheslavivna; Stepanova, Tetiana Mykhailivna (НТУ "ХПИ", 2018)
The article is devoted to the problem of improving the nutritional value of meat snack products by improving the composition of marinades with amaranth oil and mixtures for injection such as amaranth protein hydrolyzate. The authors considered the reasons for the creation of improved meat snack products with increased nutritional and biological value. The prospect of using amaranth in the composition of brine systems (mixtures for injection, massaging and soaking) for the production of meat snack products has been substantiated. The chemical composition of analogue brine systems and systems with the inclusion of amaranth is given. Use in the composition of brine for the injection of well-digestible proteins of vegetable origin is based on the fact that, together with the total increase in the moisture content of salty model fermented meat systems they allow to regulate the mass fraction of protein in the composition of finished products. Adding to the brine composition of animal protein in the amount from 0,5 to 1% allows to get meat systems with stable structural and mechanical characteristics.

Статья посвящена проблеме повышения пищевой ценности мясной снековой продукции за счет улучшения состава маринадов маслом амаранта и смесей для инъектирования - гидролизатом протеина амаранта. Авторами рассмотрены причины, приведшие к необходимости создания улучшенной мясной снековой продукции с повышенной пищевой и биологической ценностью. Обоснована перспектива использования амаранта в составе рассольных систем (смесей для инъектирования, массирования и замачивания) для производства мясной снековой продукции. Приведен химический состав аналоговых рассольных систем и систем с включением в состав амаранта
Перспективы использования амаранта в рассольных системах на основе уронатных полисахаридов
Keywords: meat snacks; uronate polysaccharides; injection; amaranth; мясные снеки; инъектирование; амарант; пищевая ценность